(3eWGQMGJ aj GdYbd hGdJfhjQ (B:s "(3YHO GdhgGH GdeSjQj CfehPLG(B" /s - (3QHhM, HTjQs ((3GdbGgQI (B:s (3QDjI ddfTQ hGdJhRjY,s, 2020)
(3cja JYGed GdeSjQj eY eaghe GdYbd aj GdadSaI GdZQHjI GdeYGUQI ? hgd HGdEecGf QO gPG GdJYOO Ydi eSJhi GdfUhU GdadSajI Edi ebhdI eYQajI hGMOI gj (B: (3ebhdI GdYbd GdeGOj ? hgd jecf GdLRe eY GdeSjQj Cf GdYbd GdeGOj gh GdeJMce GdhMjO aj eSGQGJ GdadSaI GdZQHjI GdeYGUQI ? hEPG cGf ddYbd GdeGOj fJGFL NWjQI Ydi GdadSaI GdZQHjI, acja fSJWjY JdGaj Pdc ? heG gh GdHOjd GdeYQaj GdPj GLJgO GdeSjQj aj GdOYhI Edjg HMSHGfg QDjI JLGhRjI ddYbd GdeGOj? Ef GdJYGed eY gPg GdCSFdI GdefJXeg CUdGM aj gGLS ETcGdj gjef Ydi Ybd GdeSjQj hhLOGfg, hGdPj YHQ Yfg aj fUhU eJfhYI RGNQI hZfjI HehGVjYgG hHJTGHcgG hJOGNdgG eY fUhU CNQi jbJVj efg GdEdJLGA Edi GSJQGJjLjI GdebGQHI GdJj CQi ajgG GdCSdhH GdCcKQ edGAeI aj GdJbQH ef LhgQ GdQDjI GdeSjQjI deaghe (B"(3GdYbd(B". (3ShGA CcGfJ QDjI fbOjI JahjVjI Ce QDjI HfGFjI, Jbhe HJMdjjd echfGJ GdETcGdjI Gdi YfGUQ eMOOI(B.s
(3GdeOjQ GdeSDhd (B: (3QVG YhV ; GdENQGL GdOGNdj hGdZdGa (B: (3MSjf LHjd ; NWhW GdZdGa (B: (3EHQGgje HOQ(B.s
(3HHdjhLQGajI (B: (3UaMI (B271-279.s
Keywords: (3GdeSjQj, YHO GdhgGH eMeO,s -- 1938-2008 -- (3eSGgeGJ aj GdadSaI GdYQHjIs; (3GdadSaI GdYQHjIs; (3GdadSaI GdZQHjIs; (3GdadSaI GdESdGejIs